New Treatments for Spinal Nerve Root Avulsion Injury - Carlstedt, Thomas (Frontiers in Neurology, 2016)
Further progress in the treatment of the longitudinal spinal cord injury has been made. In an inverted translational study, it has been demonstrated that return of sensory function can be achieved by bypassing the avulsed dorsal root ganglion neurons. Dendritic growth from spinal cord sensory neurons could replace dorsal root ganglion axons and re-establish a reflex arch. Another research avenue has led to the development of adjuvant therapy for regeneration following dorsal root to spinal cord implantation in root avulsion injury. A small, lipophilic molecule that can be given orally acts on the retinoic acid receptor system as an agonist. Upregulation of dorsal root ganglion regenerative ability and organization of glia reaction to injury were demonstrated in treated animals. The dual effect of this substance may open new avenues for the treatment of root avulsion and spinal cord injuries.